2019
DOI: 10.3892/etm.2019.8360
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the ED50 and ED95 of intravenous bolus of norepinephrine for the treatment of hypotension during spinal anesthesia for cesarean delivery

Abstract: Norepinephrine is considered as a potential alternative for blood pressure stabilization during spinal anesthesia for cesarean delivery, as it maintains a better maternal heart rate and cardiac output compared with phenylephrine. However, its use as a bolus dose for hypotension treatment remains largely unexplored. Therefore, the present study investigated the ED 50 and ED 95 of norepinephrine as a bolus for maternal hypotension during cesarean delivery. In the present prospective trial, 42 patients were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…Similar result was also found by Wang et al 17 In the current study, a 6 μg loading bolus of norepinephrine was given immediately following spinal anesthesia before a maintenance dose of norepinephrine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar result was also found by Wang et al 17 In the current study, a 6 μg loading bolus of norepinephrine was given immediately following spinal anesthesia before a maintenance dose of norepinephrine.…”
Section: Discussionsupporting
confidence: 91%
“…Onwochei et al 8 carried out a sequential allocation dose‐finding study and demonstrated that the ED90 of intermittent boluses of norepinephrine to prevent postspinal anesthesia hypotension was 5.8 μg (95% CI: 5.01–6.59). Similar result was also found by Wang et al 17 In the current study, a 6 μg loading bolus of norepinephrine was given immediately following spinal anesthesia before a maintenance dose of norepinephrine. To some extent, this lowered the incidence of subsequent hypotension and hypotension‐related nausea and vomiting (without a higher proportion of reflex hypertension, however).…”
Section: Discussionsupporting
confidence: 91%
“…This is the most common definition. [14][15][16] Compared to SBP at baseline, nausea or vomiting is increased when SBP decreases by 80% to 90%. 17 In our study, the 0.10 μg/ kg group had a lower frequency of nausea and vomiting, which may be explained by the low incidence of hypotension.…”
Section: Discussionmentioning
confidence: 99%